PENATALAKSANAAN FISIOTERAPI PADA KONDISI POST STROKE NON HEMORAGIK HEMIPARASE DEXTRA DENGAN MODALITAS INFRA RED (IR), NEUROMUSKULAR ELECTRICAL STIMULATION (NMES) DAN TERAPI LATIHAN DI RSUD KAJEN KABUPATEN PEKALONGAN - Hanifah Cendekia Bestari; Andung Maheswara Rakasiwi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Stroke recurrence remains a significant clinical problem, with 30% of the total 47% of patients at Kajen Regional Hospital experiencing repeated episodes. Post-stroke non-hemorrhagic right hemiparesis often results in pain, sensory impairment, motor dysfunction, coordination and balance deficits, reduced muscle strength, edema, and limitations in functional activity. This study aimed to evaluate the effectiveness of physiotherapy management using Infra Red (IR), Neuromuscular Electrical Stimulation (NMES), and Exercise Therapy modalities. A descriptive analytical case study was conducted, with data collected through heteroanamnesis and physical examination using standardized instruments: Visual Analog Scale (VAS), dermatome chart, Fugl-Meyer assessment, Manual Muscle Testing (MMT), anthropometry, non-equilibrium test, Berg Balance Scale, and Barthel Index. After four therapy sessions, results demonstrated decreased pain both at rest (VAS 3 to 2) and during movement (VAS 7 to 6), improved sensory function (0 to 1), enhanced motor performance (23 to 24), reduced edema (limb circumference difference 4 cm to 3 cm), better coordination (26 to 27), improved balance (18 to 24), and increased independence (11 to 14). In conclusion, physiotherapy with IR, NMES, and Exercise Therapy is effective in reducing pain and edema, while improving sensory function, coordination, balance, and functional independence. However, muscle strength did not show significant improvement.